Genealogi Konflik Sosial Multisektoral dan Disintegrasi Kultural di Kabupaten Bima: Sebuah Eksplorasi atas Determinan Politik, Ekonomi, dan Geospasial - Syarif Syarif; Firdaus Firdaus (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the genealogy of multisectoral social conflict and cultural disintegration in Bima Regency by examining the interplay of political, economic, socio-cultural, and geospatial determinants. Using a qualitative exploratory-critical method, the research employs content analysis, critical discourse analysis, and spatial conflict mapping based on secondary data from government reports, academic literature, and civil society documentation. The results reveal that social conflict in Bima is not simply driven by unequal access to political and economic resources, but also by structural exclusion, historical marginalization, and the erosion of traditional social values caused by uneven modernization and weak institutional performance. Politically, civil servant bias, the persistence of patronage networks, and minimal civic engagement weaken state legitimacy, public trust, and accountability. Economically, the unequal distribution of natural resources, selective access to government assistance, limited economic diversification, and unresolved agrarian disputes intensify socio-economic inequalities and rural discontent. From a geospatial perspective, the contestation over land, identity, ecological zones, and environmental resources reflects the failure of inclusive and participatory spatial development planning. The study emphasizes that the conflict is systemic, complex, and institutionalized, calling for integrated cross-sectoral policies, inclusive political reforms, and spatially participatory strategies. It advocates for institutional reform, the revitalization of local wisdom and social capital, and the reconstruction of a shared cultural identity to restore long-term social cohesion and resilience. In the context of post-decentralization Indonesia, addressing such deep-rooted, chronic conflicts requires not only strategic policy reorientation but also the empowerment of local communities to play meaningful and active roles in planning, governance, and sustainable development processes. Sustainable peace in Bima hinges on a genuine commitment to social justice, inclusive governance, ecological balance, and the preservation of cultural diversity.